Phenotypic Detection of ESBL, AmpC, MBL, and Their Co-occurrence among MDR Enterobacteriaceae Isolates - Salvia, Thounaojam; Dolma, Karma G.; Dhakal, Om Prakash; Khandelwal, Bidita; Singh, Laishram Shantikumar (Journal of Laboratory Physicians, 2022)
Background Emergence of extended-spectrum beta-lactamases (ESBLs), AmpC β-lactamases, and metallo-β lactamases (MBL), and their co-existence among members of Enterobacteriaceae pose newer diagnostic and therapeutic challenges. The present study examines the ESBL, AmpC, and MBL production by various phenotypic methods and their co-occurrence among the multidrug-resistant (MDR) Enterobacteriaceae clinical isolates.Materials and Methods Four hundred non-repetitive Enterobacteriaceae clinical isolates were collected from the Central Referral Hospital, Sikkim. The isolates were used for identification and their antibiotic susceptibility tests were performed according to the Clinical and Laboratory Standard Institute (CLSI) guidelines. ESBL was detected by double-disc synergy test (DDST) and phenotypic confirmatory disc-diffusion test (PCDDT), AmpC detection by AmpC E-test, and boronic acid disc diffusion (BD) test. MBL was detected using the imipenem–imipenem/EDTA disc and carba-NP tests.Results Around 76% were considered MDR. ESBL was seen in 58% and 50.4% based on DDST and phenotypic confirmation disc-diffusion test (PCDDT), respectively. AmpC was detected in 11.8% and 13.1% using a commercial E-test and boronic acid test, respectively. MBL were identified in 12.8% and 14.8% based on MBL imipenem-EDTA and carba-NP tests, respectively. Co-occurrence of ESBL and AmpC, ESBL and MBL, AmpC and MBL was seen in 5.2%, 11.5%, 1.3%, respectively, whereas a combination of these three β-lactamases was observed in only 0.3% of 304 MDR isolates.Conclusion The findings highlight a high prevalence of β-lactamases and their co-production among the Enterobacteriaceae, mainly in Klebsiella pneumoniae and Escherichia coli isolates. The study further highlights the necessity to identify the MDR β-lactamases stains for effective therapy in severe as well as mild bacterial infections, thereby enabling to reduce the risk of MDR in hospital and community settings.
Keywords: enterobacteriaceae; multidrug resistant; beta-lactamases; co-occurrence